Moral Intelligence Education in learning Pancasila and Citizenship Education as Strengthening the Personality of Industrial Age Students - Aprilyani S; Holifah Holifah; Menila Wati Z (CV. Rayyan Dwi Bharata, 2023)
Moral intelligence is the ability to understand right and wrong things, moral intelligence education can increase moral sensitivity in students in the industrial era. Benefits of Moral Intelligence so that an educator is able to apply or direct Moral Intelligence learning that can help students in the industrial era. The purpose of this writing is so that prospective educators and education can better understand the importance of moral intelligence in learning PPKN in elementary schools. The method used in making writing is to use the literature study method. The result of writing this journal is that an educator is more able to develop the moral intelligence of his students in learning.